Costo de financiamiento para créditos mype (micro y pequeñas empresas) a través del programa Reactiva Perú en una entidad bancaria y su competitividad en el sistema financiero peruano, 2019-2020 - Saravia Saravia, Jose Alberto (2025)
This research article aims to examine the trends in the financing costs of loans granted by Peruvian financial institutions in 2019 compared to 2020. This comparison serves to illustrate the trends in access to credit for micro and small enterprises (MSEs) and how they were affected by the crisis caused by COVID-19 in Peru.